Aktivitas Komunikasi dalam Upacara Pemberkatan Pernikahan Agama Khonghucu (Kajian Studi Etnografi Komunikasi) - Monika Herliana (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
This research is a qualitative descriptive study related to communication activities at the Confucian religious wedding ceremony in Jambi. The focus of this research is on communicative activities including situations, events, and actions of communication in wedding ceremonies with Ethnographic Communication studies. Data were obtained from observations, interviews, and supported by literature. The results of the analysis data show that during the Confucian ceremony there was a communicative situation which was conducive, sacred, familiar, and joyful. The process of marriage is sequentially described by communicative events from the beginning to the end of the procession. Communicative actions are characterized by verbal, non-verbal communication, and existing symbols. The three elements of the research results describe the communication activities which took place on the Confucian wedding ceremony. In addition, communication activities which occur have a close relationship with the concept of Confucian beliefs and teachings.